Molecular versus conventional culture for detection of respiratory bacterial pathogens in poultry - Ammar, A M; Abd El-Aziz, N K; Abd El Wanis, S; Bakry, N R (Cellular and Molecular Biology, 2016)
Acute respiratory tract infections are leading causes of morbidity in poultry farms allover the world. Six pathogens; Escherichia coli, Mycoplasma gallisepticum, Staphylococcus aureus, Pasteurella multocida, Mannheimia haemolytica and Pseudomonas aeruginosa were involved in respiratory infections in poultry. Herein, conventional identification procedures and polymerase chain reaction (PCR) were applied for detection of the most common respiratory bacterial pathogens in clinical specimens of poultry obtained from 53 Egyptian farms with various respiratory problems and the results were compared statistically. The analyzed data demonstrated a significantly higher rate of detection of the most recovered microorganisms (P<0.05) by PCR comparing to classical culture procedures. Further, multiplex PCR could detect E. coli, M. gallisepticum, S. aureus and Ps. aeruginosa in a single reaction, however, M. haemolytica was reported in a uinplex system. According to PCR results, the most commonly recorded bacterial pathogens in examined poultry farms were E. coli and Ps. aeruginosa (54.71% each), followed by M. haemolylica (35.85%) and M. gallisepticum (20.75%). In conclusion, PCR assay offered an effective alternative to traditional typing methods for the identification and simultaneous detection of the most clinically relevant respiratory pathogens in poultry.